The Role and Impact of Agricultural Machinery Service Provider for Rural Community Development Case in Indonesia - Winarno, Kodrad; Sulastiyah, Amie; Rusliyadi, Muhamad (International Journal of Publication and Social Studies, 2021)
Agricultural machinery plays a strategic role in achieving Indonesia’s agricultural development goals. It is considered capable of increasing agricultural production and productivity through managing cultivation, harvest and post-harvest activities. The government has facilitated farmers with agricultural machinery through farmer groups and joint-farmer groups by encouraging them to form Agricultural Machinery Services Provider (AMSP). The purpose of this research is to describe the agribusiness management of AMSP, in terms of organizational, technical and economic aspects. This research was conducted from June 2017 to October 2017 in four districts, namely Bantul, Sleman, Gunung Kidul and Kulon Progo. Purposive sampling was used as a sampling method in this research. There were 32 respondents; 12 from AMSP, 16 from farmers groups, 4 private agricultural machinery service providers. The data analysis used was descriptive and qualitative data analysis. This research concluded that management of AMSP from an organizational perspective in the 4 districts is compatible with the Permentan Nomor 25 2018 guidelines regarding growth and development of AMSP. From the technical aspect, most of the operational agricultural machinery is 2-wheeled and 4-wheeled tractors. From the economic aspect, Earnings are distributed based on 40:60 ratio where AMSP earns 40% and the operator earns 60%. In relation to the cost of land cultivation, AMSP can earn between RP. 600.000,- – Rp. 800.000,- and the operator can earn Rp. 900.000,- – Rp. 1.200.000,-.